2020
DOI: 10.1002/jemt.23511
|View full text |Cite
|
Sign up to set email alerts
|

Developing ofN‐(4‐methylpyrimidine‐2‐yl)methacrylamideLangmuir–Blodgettthin film chemical sensor via quartz crystal microbalance technique

Abstract: In the present work, the characterization and gas sensing properties of newly synthesized N‐(4‐methylpyrimidine‐2‐yl)methacrylamide (N‐MPMA) monomer Langmuir–Blodgett (LB) thin films were investigated. The UV–visible spectroscopy, quartz crystal microbalance (QCM), and atomic force microscopy were utilized to characterize N‐MPMA LB thin films. The surface behavior of N‐MPMA monolayer was stable and allowed an effective transfer at a surface pressure of 14 mN/m. The mass change/unit area value of the N‐MPMA LB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is necessary to clarify the question of the influence of LB films on the properties of acoustic waves to use them as sensor coatings. The influence of LB films on the characteristics of devices based on surface and bulk acoustic waves [52][53][54], Love waves [55], FBAR [56], and HF SAW resonators [57] was studied. As a result, it was shown that these films have almost no effect on the characteristics of acoustic waves of various types and can be effectively used as sensor coatings.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to clarify the question of the influence of LB films on the properties of acoustic waves to use them as sensor coatings. The influence of LB films on the characteristics of devices based on surface and bulk acoustic waves [52][53][54], Love waves [55], FBAR [56], and HF SAW resonators [57] was studied. As a result, it was shown that these films have almost no effect on the characteristics of acoustic waves of various types and can be effectively used as sensor coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the applications include superconducting technology devices such as high film magnets, rotating magnetic devices and power cables and electronic devices, diodes, hard coatings and optical coatings, solar cells, and batteries. Recently, thin films are used as sensors for sensing gases [2], temperature [3], humidity [4], pressure [5], material ions [6], forces [7], chemicals [8], etc.…”
Section: Introductionmentioning
confidence: 99%